PENGARUH IKLIM KERJA PERUSAHAAN DAN DESAIN PELATIHAN TERHADAP MOTIVASI KERJA KARYAWAN PT. PLN (PERSERO) UBS P3B JAWA BALI - Leliana, Intan; Latief, Abdul Madjid (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2016)
Recruitment, advancement of technology and working methodology, competition and the development of the company’s productivity as well as an adjusment of the company’s policy are the many reasons a company should train the employees (Hariandja, 2002). Training can be given by sending the employees to other institution or conduct an internal training trained by internal instructors from the company or work together with other institution to design, to provide the instructor and conduct the process of the training. This thesis tries to analyze the influence of working climate and training design toward working motivation of the employees. This hypothesis is made in order to test a theory on training process. The hypothesis is tested based on the data derived from distributing questionaire to 32 participants of englishfor engineering training held by PT.PLN P3B Jawa Bali. This thesis is a quantitative descriptive research. The approach applied in this thesis is survey. The technique of data analysis is path analysis that is proccesed by SPSS 17 Program. The primary data is obtained from giving questionaire to 32 respondents and the secondary data is obtained from interview and other supporting data from the USB P3B Jawa Bali as the company where the research is conducted and also from Learning Center as an institution partner that holds the program. The Result of the study surprisingly reveals that there is no correlation between working climate and training design, and between training design and working motivation the only significant correlations is between working climate and working motivation. Keywords : Organization climate, Training Desain and Working Motivation